Clinical and Epidemiological Profile of Breast Cancer in Mexico: Results of the Seguro Popular - Nancy Reynoso-Noverón (Journal of Global Oncology, 2017)
Purpose: One half of the Mexican population lacks comprehensive health care coverage. In 2003, a reform to the General Health Law was approved that led to the creation of the System of Social Protection in Health and made universal health coverage mandatory. The main innovation of this reform was Seguro Popular, which provided coverage for breast cancer. Here we report the outcomes of women with breast cancer treated at a cancer center in Mexico under Seguro Popular. Materials and Methods: This was a retrospective cohort study that included all patients with breast cancer treated in the Instituto Nacional de Cancerología in Mexico City between January 2007 and December 2013 with Seguro Popular coverage. Demographic and clinical information were collected and survival outcomes were analyzed. Results: A total of 4,300 women with breast cancer were included in this analysis. Most patients had locally advanced disease at diagnosis (53%, n = 2,293), and 13% (n = 558) presented with stage IV disease. Neoadjuvant chemotherapy was administered to 1,834 patients (52%), with a pathologic complete response in 25.1% (n = 460). Median follow-up was 40.5 months. Five-year survival for the entire cohort was 82% (95% CI, 81% to 84%). Five-year survival was 97% for early-stage disease (95% CI, 95% to 98%), 82% for locally advanced disease (95% CI, 80% to 84%), and 36% for metastatic disease (95% CI, 30% to 42%). Conclusion: This represents the first description of a cohort of patients with breast cancer treated in Mexico under Seguro Popular. Seguro Popular has allowed our institution, and other Mexican centers, to establish efficient standardized mechanisms to treat patients with breast cancer.